1992
DOI: 10.1016/s0022-5347(17)37674-7
|View full text |Cite
|
Sign up to set email alerts
|

Site of Deafferentation and Electrode Placement for Bladder Stimulation: Clinical Implications

Abstract: Based on the clinical experience of treating neurogenic bladders by the electrical stimulation of the ventral sacral roots, neuroanatomical and neurophysiologic studies were designed to study the mechanism of detrusor-sphincter dyssynergia during electrical stimulation of the sacral roots. An experimental model was developed to decrease the stimulation response of the pelvic floor and external urethral sphincter muscles while preserving bladder contraction. The significance of the site of deafferentation and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
4

Year Published

1996
1996
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 16 publications
1
10
0
4
Order By: Relevance
“…Throughout the course from their originating point to their exit from the dura, the rootlets maintain their identity as separate bundles that can be dissected under magnification. These results are in accordance with those found by Hohenfellner et al (1992). This made it possible for microelectrode techniques to stimulate groups of neurons and axons innervating the bladder detrusor in the sacral spinal cord, without simultaneous excitement of the EUS.…”
Section: Discussionsupporting
confidence: 91%
“…Throughout the course from their originating point to their exit from the dura, the rootlets maintain their identity as separate bundles that can be dissected under magnification. These results are in accordance with those found by Hohenfellner et al (1992). This made it possible for microelectrode techniques to stimulate groups of neurons and axons innervating the bladder detrusor in the sacral spinal cord, without simultaneous excitement of the EUS.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies showed that the sacral root emerged from the ation and, if successful, will represent a significant advance in achieving bladder control. The findings of spinal cord in several rootlets [12], prompting our attempt to stimulate the rootlets. The preliminary success this study will be implemented in current clinical trials to improve the selectivity and responsiveness of sacral in obtaining more selective responses by stimulating individual rootlets than by stimulating the total sacral root implants.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of the ventral sacral roots after de-afferentation, in most cases, induces bladation holds true for the dorsal root also). In a previous study [12] we advocated intradural de-afferentation of der contraction and bladder evacuation.…”
Section: Introductionmentioning
confidence: 99%
“…Pudendal nerve anastomoses are carried out to innervate a functioning neosphincter in patients having undergone a rectal excision (Sato et al, 1997). Electrodes may be placed on the pudendal nerve (or its root or branches) to treat anal or urethral sphincter insufficiency (Hohenfellner et al, 1992).…”
Section: Introductionmentioning
confidence: 99%